2013
DOI: 10.3846/btp.2013.08
|View full text |Cite
|
Sign up to set email alerts
|

The Dimensions of Customer Preference in the Foodservice Industry

Abstract: Abstract. Today's foodservice industry management must place a high priority on understanding the growing markets resulting from rapid urbanization and rising numbers of tourists. This industry has a huge impact on the global economy but it is affected by customers' ever-changing preferences. Managers need to gain and sustain strategic advantage in this highly competitive industry, thus a local customer preference assessment is crucial. This paper presents the dimensions of customer preference in the food serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 57 publications
1
15
0
3
Order By: Relevance
“…It covered brand image of the restaurant and uniqueness of brand name. This study is aligned with the previous research that stated factors influencing decision to select restaurants [12,[13][14][15][16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It covered brand image of the restaurant and uniqueness of brand name. This study is aligned with the previous research that stated factors influencing decision to select restaurants [12,[13][14][15][16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 86%
“…They will have considerations that may differ from one to another. This is due to different cultural, ethnic, and economic backgrounds tangibles [19]. According to study by Azim et al factors included are food quality and taste, cleanliness, physical environment, staff cooperation, suitable environment for family gathering, privacy, and preferential treatment [20].…”
Section: Introductionmentioning
confidence: 99%
“…Along with the market aspect of ebike, the safety practices also required to publicize the same. A study by Abdullah et al (2013) has confirmed that the customer preference and their order of importance, price, quality of service, branding are considered to be the important customer dimensions in au tomobile industry. Knowing these dimensions relative influ ence may result in better allocation of resources for effective services in electric vehicle industry.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Actually, the application of sharia principles in the banking industry has become an imperative part of the financial industry, such as in the United Kingdom, Switzerland, Italy, and Germany (Abdullah et al 2011, Ismal 2012. Based on a survey by Re-pucom (Nielsen Sports) in 2013 with the sample amounted to 1,000 inhabitants by age 16-69 years, showed that 77% of the population of Indonesia loves football, which is slightly below Nigeria that reaches 83% of the population.…”
Section: Introductionmentioning
confidence: 99%